2016
DOI: 10.5812/ircmj.21471
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Implementing Evidence-Based Intrapartum Care: A Descriptive Exploratory Qualitative Study

Abstract: Background:Evidence based practice is an effective strategy to improve the quality of obstetric care. Identification of barriers to adaptation of evidence-based intrapartum care is necessary and crucial to deliver high quality care to parturient women.Objectives:The current study aimed to explore barriers to adaptation of evidence-based intrapartum care from the perspective of clinical groups that provide obstetric care in Iran.Materials and Methods:This descriptive exploratory qualitative research was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 32 publications
5
43
0
Order By: Relevance
“…A study undertaken in Iran between 2013 and 2014 showed that key barriers to adopting evidence-based practices were lack of knowledge and skills, lack of motivation to change or adopt new behavior, lack of decision-making authority, fear of legal action, and poor health professional-patient communication. Other significant barriers included shortage of equipment and inappropriate physical structure of birth settings and the fact that the decisions taken by doctors often go against the norms of best practice 21 . Both studies showed that women had limited capacity to influence change [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…A study undertaken in Iran between 2013 and 2014 showed that key barriers to adopting evidence-based practices were lack of knowledge and skills, lack of motivation to change or adopt new behavior, lack of decision-making authority, fear of legal action, and poor health professional-patient communication. Other significant barriers included shortage of equipment and inappropriate physical structure of birth settings and the fact that the decisions taken by doctors often go against the norms of best practice 21 . Both studies showed that women had limited capacity to influence change [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…However Iranian midwives today have little authority in providing childbirth care and for the most part the perinatal care process is managed by obstetricians in teaching hospitals. In some non-teaching public hospitals, childbirth care is performed by midwives under the obstetricians' supervision [20].…”
Section: Setting and Participantsmentioning
confidence: 99%
“…These findings are consistent with other studies in low‐ and middle‐income countries. For example, workforce shortages and heavy workload were identified as key barriers to evidence‐based nursing care in Iran (Iravani, Janghorbani, Zarean, & Bahrami, ) and to quality midwifery care in Philippines and Indonesia (Filby, McConville, & Portela, ). Lack of material resources such as equipment, supplies and facilities were identified as significant barriers to optimal surgical care in India and Bangladesh (Grimes, Bowman, Dodgion, & Lavy, ) and in the implementation of maternal and perinatal health guidelines in Myanmar (Vogel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another project‐specific barrier identified in the current study was related to consumers’ knowledge, beliefs and financial resources. It is quite unexpected that only one project acknowledged this issue, given that many studies in low‐ and middle‐income countries have reported poor health literacy, patients’ misconceptions and financial constraints as key barriers to the delivery of EBHC (Iravani et al., ; Ritchie et al., ). Even though implementation studies tend to focus on organizational and health provider factors and less so on consumers and least of all on policymakers, the literature supports a multilevel analysis in which implementation planning equally involves examining those who receive health care (i.e., consumers and community; Ritchie et al., ; Vogel et al., ) as well as the government system responsible for regulating health policies and reforms (Mosquera et al., ; Ritchie et al., ).…”
Section: Discussionmentioning
confidence: 99%